Svalbard and Conflict Management in a Changing Climate: A Risk Based Approach - Ash, John (Nordlit, 2020)
Conflict in the Arctic is nothing new, and Svalbard is a geographical confluence of factors that create the potential for inter-group violence. The purpose of this paper is to explore those factors, identifying approaches to the evaluation of their associated risk. The emphasis is on biomarine resources, which at present constitute the most likely focus for escalating disputes. Contributory factors, including the catalytic effects of climate change, will also be considered. Given the political progress that has been achieved recently, the most likely situation for an intense interstate conflict in the short term is one that spreads tothe Arctic, rather than one igniting within it. However, as the century progresses, dormant problems relating to the Svalbard archipelago will combine with environmental, economic and political trends to exacerbate conflict risk. Traditionally, armed conflict has been viewed as a phenomenon that cannot be predicted. This view is identified as dangerously misleading. Using a risk based approach and noting advances in analytical techniques, representative scenarios in which conflict may occur are examined and prospective methods of risk management identified.